Clinical characteristics of dengue virus infections in Karachi from 2019 to 2023: a cross-sectional study - Khalid Mahmood; Muhammad Rashid; Sabeeta Kanwal Ansari; Fatima Kanani; Thomas Iftner (Scientific Reports)
Abstract Dengue fever is a vector-borne, acute, febrile, and self-limiting systemic viral infection that affects tropical and subtropical regions, including Pakistan. Karachi has a significant burden of Aedes aegypti and Aedes albopictus due to suitable breeding sites, weather, and rapid and unplanned urbanization of squatter areas. The country has limited surveillance studies on circulating serotypes of the dengue virus and the patient’s clinical features evolving over temporal changes. This study aimed to bridge the gap by screening 1500 patients using immunochromatographic detection and clinically following up on 486 of them. RNA extraction and cDNA synthesis of positive patients were performed, followed by PCR and sequencing. Data analysis and graphs were done on Prism 8.0. Males (53.87%) had a higher infection rate than females (46.13), with ages 18–60 years having the highest infection rate (69.14%). Results showed that 57.8% of patients were positive for NS1, followed by IgM (39.8%), and IgG (89.77%). DENV 1 and DENV 2 were found to be circulating, representing 20% and 80% respectively. Data on fever, shortness of breath, body aches, headache, nausea, vomiting, diarrhea, and epistaxis revealed significant differences. We conclude that continuous surveillance of dengue and other Flaviviruses and their infections is necessary to improve the prognosis and management of vector-borne diseases, thereby reducing the associated mortality rate of patients in Pakistan.